2019
DOI: 10.1101/638296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Septin 2/6/7 complexes tune microtubule plus end growth and EB1 binding in a concentration- and filament-dependent manner

Abstract: Septins are filamentous GTP-binding proteins, which affect microtubule-dependent functions including membrane trafficking and cell division, but their precise role in microtubule dynamics is poorly understood. Here, in vitro reconstitution of microtubule dynamics with SEPT2/6/7 complexes, the minimal subunits of septin heteromers, shows that SEPT2/6/7 stabilizes and pauses microtubule plus ends in their growth phase, and inhibits tracking of the microtubule plus end protein EB1 in a concentration-dependent man… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…1G). This biphasic effect resembled the increase and diminution of microtubule plus end growth by nanomolar and micromolar Sept2/6/7 concentrations, respectively, which corelates with a transition of Sept2/6/7 from oligomers to higher-order polymers with increasing concentrations (9). Coating microtubules with mCherry-Sept2/6/7 showed that septins are present along the actin-bound microtubule lattice (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…1G). This biphasic effect resembled the increase and diminution of microtubule plus end growth by nanomolar and micromolar Sept2/6/7 concentrations, respectively, which corelates with a transition of Sept2/6/7 from oligomers to higher-order polymers with increasing concentrations (9). Coating microtubules with mCherry-Sept2/6/7 showed that septins are present along the actin-bound microtubule lattice (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…To test whether septins interact directly and concomitantly with both actin and microtubules, crosslinking them together, we performed in vitro binding assays using stable prepolymerized microtubules, actin filaments and septins. We purified recombinant Sept2/6/7, the minimal septin complex which has been shown to bind separately actin and microtubules (9, 10). Using total internal reflection fluorescence (TIRF) microscopy, we assayed for the association of immobilized glass-bound Sept2/6/7-coated microtubules with actin filaments that were floated into the imaging chamber.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this possibility, septins (SEPT2/6/7, SEPT9) preferentially associate in vitro with microtubule lattices bound to the stable GTP analog GMPCPP (guanylyl-αβ-methylenediphosphonate) which are characterized by a non-compacted longitudinal inter-dimer interface similar to that of taxol-stabilized protofilaments [32][33][34] (Figure 1A). Microtubule bundling may further enhance septin binding, but it is unknown whether the parallel or antiparallel orientation of bundled microtubules plays a role.…”
Section: Septins: Multimeric Gtpases With Microtubule-and Membrane-binding Specificitiesmentioning
confidence: 85%
“…SEPT9 associates with unpolymerized tubulin, and microtubuleassociated SEPT9 recruits tubulin dimers to the microtubule lattice, and thereby may rescue microtubule lattices from depolymerization and also repair sites of damage [33]. In vitro assays show that SEPT9 and SEPT2/6/7 complexes promote microtubule growth and elongation by suppressing catastrophe [32,33] (Figure 1C). In agreement with the in vitro findings, septins associate with microtubule bundles and promote as well as guide microtubule growth in living cells [28].…”
Section: Glossarymentioning
confidence: 99%
See 1 more Smart Citation